Cloud chamber laboratory investigations into scattering properties of hollow ice particles. (May 2015) - Smith, Helen R.; Connolly, Paul J.; Baran, Anthony J.; Hesse, Evelyn; Smedley, Andrew R.D.; Webb, Ann R.
Abstract: Measurements are presented of the phase function, P 11, and asymmetry parameter, g, of five ice clouds created in a laboratory cloud chamber. At −7 °C, two clouds were created: one comprised entirely of solid columns, and one comprised entirely of hollow columns. Similarly at −15 °C, two clouds were created: one consisting of solid plates and one consisting of hollow plates. At −30 °C, only hollow particles could be created within the constraints of the experiment. The resulting cloud at −30 °C contained short hollow columns and thick hollow plates. During the course of each experiment, the cloud properties were monitored using a Cloud Particle Imager (CPI). In addition to this, ice crystal replicas were created using formvar resin. By examining the replicas under an optical microscope, two different internal structures were identified. The internal and external facets were measured and used to create geometric particle models with realistic internal structures. Theoretical results were calculated using both Ray Tracing (RT) and Ray Tracing with Diffraction on Facets (RTDF). Experimental and theoretical results are compared to assess the impact of internal structure on P 11 and g and the applicability of RT and RTDF for hollow columns. Abstract : Highlights: Two different structures of hollow ice crystal were found at −7 °C and −30 °C. Particle models were created and tested with Ray Tracing and RTDF. Modelled results show the shape of the cavity affected the asymmetry parameter. Phase functions were measured for five clouds consisting of different particle types. Compared to measured results, models typically over predicted asymmetry parameter.